Sistem Hukum Perkawinan Pada Negara Hukum Berdasarkan Pancasila - Tengku Erwinsyahbana (Fakultas Hukum Universitas Riau, 2012)
Marriage is included as basic needs (rights) of every human being, whose goal is to establish a family or household who are happy and eternal by Belief in God Almighty. The inclusion of elements of the phrase